A speciation study of various Pt(II) and Pt(IV) complexes including hexaaquaplatinum(IV) by means of 195Pt NMR spectroscopy, in support of a preliminary study of the oxidation mechanism of various Pt(II) complexes - Murray, Pieter (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.